Quasi-pseudometrizability of the point open ordered spaces and the compact open ordered spaces - Koena Rufus Nailana (International Journal of Mathematics and Mathematical Sciences)
We determine conditions for quasi-pseudometrizability of the point open ordered spaces and the compact open ordered spaces. This generalizes the results on metrizability of the point open topology and the compact open topology for function spaces. We also study conditions for complete quasi-pseudometrizability.